Nutritional consequences on the outcome of parasitic challenges on small ruminants - Athanasiadou S.; Kyriazakis I.; Giannenas I.; Papachristou T.G. (Nutritional and foraging ecology of sheep and goats, 2009)
Host nutrition can affect the resident and incoming populations of pathogens and consequently ameliorate the detrimental consequences of an infectious challenge in small ruminants in four different ways: (i) affect the fitness of the parasite, through the ingestion of plant compounds, such as plant secondary metabolites; (ii) alter the conditions in the gut environment from beneficial to detrimental and even toxic for parasite survival; (iii) positively affect host resistance, i.e. the ability of the host to regulate gastrointestinal nematode establishment, development, fecundity and survival; and (iv) enhance host resilience to the parasitic infection. In this paper we address the effects of nutrition either directly on parasite fitness or through its influence on the environment of the parasite. We believe the nutritional consequences on parasitised hosts have not received appropriate attention so we focus on them in this paper. We first discuss how the excess or lack of nutrients can alter the physicochemical properties of the digestive tract making this environment more hostile for parasites transmitted through the oral route. We then concentrate on specific plants rich in secondary metabolites (PSM) and review evidence on the consequences of their consumption on resident or incoming nematode population. We conclude by discussing specific prerequisites for effectively using nutrition for parasite control.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)